Pomen notranje integracije javnega potniškega prometa za izboljšanje njegove ponudbe - Plevnik, Aljaž (Urbani izziv, 2004)
The article summarises some of the findings of the research Development possibilities for development of public transport and settlement in the Republic of Slovenia, which is one of the first attempts at comprehensive dealing with public transport in the country. Integration of public transport is defined, as well as its significance for development of this system. Amongst the wide palette of possible types of integration we limited the article to internal integration of the pubic transport system, which is of keyimportance for fulfilling its potential in the wider transport system. Withits three forms (physical, pricing and logical), internal integration can contribute to higher attraction and utility of public transport.
Keywords: cestni promet; javni promet; mestni promet; prometno omrežje; prostorsko planiranje; spatial planning